The Persistence of Evaluation Disparities - Knetsch, Jack L.; Sinden, J. A. (Quarterly Journal of Economics, 1987)
Jack L. Knetsch, J. A. Sinden; The Persistence of Evaluation Disparities*, The Quarterly Journal of Economics, Volume 102, Issue 3, 1 August 1987, Pages 69